POLA ASUH ORANG TUA DALAM MENANAMKAN NILAI-NILAI AGAMA AUD PADA KELUARGA PETANI MELATI DESA DARAMISTA LENTENG SUMENEP - Arifah, Nur Aina; Annufus, Nabila; Uyun, Nadhiratul (Thufuli, 2023)
Children's first education comes from the family. The family is the smallest social group in society, generally consisting of father, mother and children. Therefore, it is the duty of parents to educate them to obey Allah SWT according to the stages of their development. However, not all parents have the ability to implement effective parenting. This study attempts to describe parenting patterns and obstacles in developing religious values in children in Daramista Lenteng Village, Sumenep. Interviews, observations, and documentation are data collection techniques used to have more in-depth information regarding the types of parenting styles used and the obstacles faced by parents in developing religious values in early childhood. Informants of this study were selected through a purposive sampling technique with the following criteria; parents work as jasmine farmers, have children aged 4-6 years, and apply this type of parenting pattern. The results of this study indicate that the parenting style applied by parents to farming families in Daramista Lenteng Sumenep Village is democratic parenting. Meanwhile, the obstacles faced by parents on average are related to the lack of alternative solutions in dealing with parenting problems so that the approach chosen sometimes tends to be ineffective.